Peran dan Upaya Direktorat Jenderal Bea dan Cukai dalam Meminimalisir Meningkatnya Tindak Pidana Kepabeanan Bersumber UUD 1945 dan NKRI - Anis Riski Yulianti; Edy Soesanto; Alffin Suherzan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
International trade is something that often occurs in customs areas. Customs areas often witness international trade. Law on 17 of 2006 and Law on Excise No 11 of 1995 stipulate regulations regarding customs. However, in the case of exports and imports, it is difficult to differentiate between customs violations and customs crimes. The Customs and Excise Agency, an institution under the Ministry of Finance, is needed to handle customs cases. Based on the questions we discussed, the role and efforts of the DJBC in minimizing the increasing number of customs crimes must be discussed. The increase in customs crimes and obstacles. In their efforts to reduce the increase in customs crime, Customs and Excise is facing challenges. It is important to note that the national principles that drive the duties and efforts of the DJBC to reduce the increasing level of customs crimes can be linked to the principles and principles reflected the 1945 Constitution. Attributes of the Unitary State of the Republic of Indonesia (NKRI) including nationalism and patriotism, sovereignty and territorial integrity, law and order, shared prosperity, and security.